AN INVESTIGATION ON LIGHT COLOR AND STOCKING DENSITY ON SOME PRODUCTIVE PERFORMANCE OF BROILERS - Mudhar A. S. Abu Tabeekh; Riyad K. Mosa; Rabia J. Abbas (Basrah Journal of Veterinary Research)
This study was designated to investigate the effect of light color and stocking density on some productive performance of broilers. A total of 675 Ross 308 one-dayold broiler chicks were used in this study. The birds were exposed to white light (WL) as a control , red light (RL), blue light (BL), green light (GL), and Blue – Green mix light (BGL) by a light-emitting diode system (LED) applied for 24 hours daily in separated rooms. The birds were randomly divided and housed into 9 wooden sealed pens of 1m2in three replicates for each density 12, 15 and 18 birds/m2in the room. The results showed that the broilers reared under BGL significantly increased (P< 0.05) body weight (BW) and weight gain (WG) at 1st, 3rdand 5thweek. Obviously, stocking density had no significant effect on BW and WG at 1stweek but significantly increased under 12 birds/m2at 3rdand 5thweek. Feed intake (FI) recorded a significant increase (P< 0.05) in broilers reared under WL at 1stweek, but no statistical difference was found at 3rdweek whereas, FI significantly increased (P< 0.05) in broilers reared under BL at 5thweek. The stocking density affected FI values which were significantly differed (P< 0.05) at 1st, 3rdand 5thweek under 12 birds/m2compared with other densities. The results of the study revealed a significant increase (P< 0.05) of Feed conversion ratio (FCR) in broilers reared under BL at 1stweek and RL at 3rdweek but there was no significant difference between groups at 5thweek. The results indicated a significant difference of FCR value in 18 birds/m2at 1st week but there were no significant differences at 3rdand 5thweek at different densities. In conclusion, the results of this study indicated that chickens reared under five different color lighting schedules with three bird densities showed that broilers reared under mixing blue – green light under 12 birds/m2has a significant positive effects on production performance compared with other light programs and bird densities